Tranquilizing and Allaying Excitement Needling Method Affects BDNF and SYP Expression in Hippocampus. (6th July 2017) - Zheng, Peng; Xu, Xiaohong; Zhao, Hongyan; Lv, Tingting; Song, Bailin; Wang, Fuchun
Abstract : Sleep disorder is a state of sleep loss caused by various reasons, which leads to a series of changes, such as emotion, learning and memory, and immune function. "Tranquilizing and allaying excitement" was widely used in clinical treatment of insomnia; however, the mechanism was still not very clear. We randomly divided rats into three groups: control group, sleep deprivation group, and acupuncture treatment group. We observed BDNF and SYP expression in hippocampus in these three groups. Both protein contents and mRNA contents of BDNF and SYP were measured by western blot, immunohistochemistry, and RT-PCR analysis. The sleep deprivation model was established using modified multiple platform sleep deprivation method (MMPM). Our study explored the BDNF and SYP abnormality in hippocampus caused by sleep deprivation and "tranquilizing and allaying excitement" intervention regulated the abnormal expression of BDNF and SYP caused by sleep deprivation on the short run and the long run. Our study provided a molecular evidence that "tranquilizing and allaying excitement" treatment in rats with sleep disorder affects learning and memory ability.